Ubiquitous Computing: Any Ethical Implications? - Gonzalez, José Artur Quilici; Koyabashi, Guiou; Broens, Mariana Cláudia [UNESP]; Gonzalez, Maria Eunice Quilici [UNESP] (IGI Global, 2010)
In this article, the authors investigate, from an interdisciplinary perspective, possible ethical implications of the presence of ubiquitous computing systems in human perception/action. The term ubiquitous computing is used to characterize information-processing capacity from computers that are available everywhere and all the time, integrated into everyday objects and activities. The contrast in approach to aspects of ubiquitous computing between traditional considerations of ethical issues and the Ecological Philosophy view concerning its possible consequences in the context of perception/action are the underlying themes of this paper. The focus is on an analysis of how the generalized dissemination of microprocessors in embedded systems, commanded by a ubiquitous computing system, can affect the behaviour of people considered as embodied embedded agents.
Keywords: Ubiquitous computing; perception-action; affordances; Ethics; Ecological Philosophy